Effects of Polyethylene and Polystyrene Blending on Pyrolysis of polypropylene - Chareunchai, Wanida; Nakpipat, Dr. Paisal; Wattananusorn, Santi (Engineering and Applied Science Research, 2013)
This research studied the effect of other plastics blending on the degradation of polypropylene by mixing polyethylene and polystyrene as impurities with polypropylene in concentrations of 20%, 40%, 60% and 80% by weight and pyrolysing under nitrogen atmosphere. From the thermal analysis by Thermo gravimetric analyzer (TGA), it is found that the virgin polypropylene was degraded at 330 – 495 ºC and that for polyethylene blending on polypropylene, the temperature of degradation was increased to the range of 360 – 510 ºC and for polrstyrene blending on polypropylene, temperature was decreased to the range of 340 – 500 ºC. The pyrolysis of plastics mixtures in various ratios at 300 – 500 ºC gave oil, gas and residue as product. The oil and gas are mixture of micro – molecular hydrocarbon and their derivatives which could be served as feedstock for light olifins manufacture in the same way as crude petroleum